Capacitance study of integrated circuits matrix interconnects - Ahcene Lakhlef; Arezki Benfdila; Lounas Belhimer (Institute of Advanced Engineering and Science, 2021)
Propagation delays and couplings between nearby lines affect the circuit performances (speed, power consumption) and operations. Propagation delays in longer lines can become critical compared to the clock frequency and can induce unwanted signals in neighboring lines (